Intragame blood-lactate values during ice hockey and their relationships to commonly used hockey testing protocols - Noonan, B. C. (The Journal of Strength and Conditioning Research, 2010)
This study evaluated the on ice blood-lactate values during a division 1 ice hockey game in an attempt to demonstrate the highly variable nature of the game. Our hypothesis was that intragame blood-lactate (BLa) values would be highly variable and related to shift length. Six men (age = 20.4 + 1.8 years, body mass 81.3 +8.7 kg) agreed to have fingerstick BLa samples taken at the completion of selected shifts (n = 35 samples) during the first and third periods of a division 1 ice hockey game. Shift length including work and rest intervals were also recorded for each of these shifts. Blood-lactate values ranged from 4.4 to 13.7 mmol/L with a mean value of 8.15 (+2.72) mmol/L. Shift length ranged from 55 to 145 seconds with individual work intervals within the shifts ranging from 29 to 102 seconds in length. Most shifts had either 1 or no play stoppages and rest to work intervals ranged from 0-1.66 (+0.53). These results further support the intense and variable nature of ice hockey and should help coaches develop more specific training and testing regimens to prepare for these demands. They also highlight the need for a validated and reliable test of repeated sprint ability for ice hockey players.